Natural dye coated nanocrystalline Tio2 electrode films for DSSCs - Mohamad, Souad A.; Alaei, Iraj (IIUM Press, 2011)
Nanocrystalline TiO2 thin films were successfully prepared by dip-coating technique on ITO conductive glass substrates at low temperature. Dye-sensitized solar cells based on these films have exhibited high overall light-to-electricity conversion efficiency of 4.67 % under illumination intensity 100 mW/cm2.